2006: The Topology of Morals (Who Does the Algorithm Think We Are?). Issue 2 (May 2021) - Eloff, Aragorn
Abstract : Deleuze's Postscript on the Societies of Control has been the most common entry point for interrogating the ways in which contemporary digital technologies have altered the social and the subjective from a Deleuzo-Guattarian perspective. It is, however, in A Thousand Plateaus that we find the most comprehensive set of resources for grappling with the Algocene, the contemporary digitally interconnected world of ubiquitous computing, drones, data mining, smart cities, social media, automated trading and other data-driven technologies that are heavily reliant upon algorithmic processes and deep learning networks. In this broad survey, I argue that in order to grapple with these new technological assemblages and the implications of their deployment across society, we should posit a new major stratum, the algoplastic, and, along with it, new modes of operation of order-words and the regimes of signs they form part of. I conclude by posing some of the new problems that emerge with the Algocene.